A Retrospective Analysis of Malaria Trends in Maksegnit Health Center over the Last Seven Years, Northwest Ethiopia: 2014-2020. (24th May 2022) - Eshetu, Tegegne; Muhamed, Bedruzeman; Awol, Merima; Kassa, Zebie; Getu, Mehabaw; Derso, Adane; Abere, Aberham; Zeleke, Ayalew Jejaw
Abstract : Background . In Ethiopia, despite various public health intervention approaches have been implemented to eliminate malaria, its public health problem remains considerable. There are such numerous studies; however, investigating the trend of malaria infection in various settings is paramount for area-specific evidence-based interventions, evaluating ongoing malaria control programs. Hence, since the trend of malaria infection in Maksegnit has not yet been documented, this study is aimed at assessing the seven-year trend of malaria in Maksegnit Health Center. Methods . An institutional-based retrospective study was conducted to assess the trend of malaria prevalence over the last seven years (2014-2020) using recorded blood smear reports in the laboratory logbook in Maksegnit Health Center, Northwest Ethiopia. Result . Over the last seven years, a total of 28217 clinically malaria-suspected individuals were requested for blood film examination at Maksegnit Health Center. Of whom, microscopically confirmed malaria case was found in 4641/28217 (16.4%). A significant seasonal and interannual variation of malaria cases was observed (P < 0.001 ). The highest prevalence was observed in years 2014 (25.5%) and 2020 (25.1%), while the minimum annual prevalence was seen in 2017/18 (6.4%). The month of October (25.5%) had the highest number of malaria cases documented, while February had the least (4.7%). Males and individuals under the age group of 15-45 were the most affected segments of the population. A significant interannual fluctuating prevalence of malaria cases was recorded ranging from 25.5% to 6.4% (P < 0.001 ). Conclusion . Malaria is still a public health threat in the study area despite significant fluctuating patterns of malaria was observed in the last seven years. In particular, a bounced back trend of malaria from 2018 to 2020 is alarming. Thus, the implementation of ongoing intervention approaches should be reconsidered, and uninterrupted efforts of the concerned bodies are still needed.